PERSEPSI SISWA EFL TERHADAP PENGGUNAAN BAAMBOOZLE DI PEMBELAJARAN KOSAKATA - Alifia Rifda Arini; Pratnyawati Nuridi Suwarso (STKIP Siliwangi, 2024)
Various methods are used to allow students to be more involved in a meaningful vocabulary learning atmosphere, one of which is using technology-based gamification. This study aims to investigate EFL learners’ perception of technology-based gamification using Baamboozle for English vocabulary learning. Accordingly, following this objective, a qualitative approach was used, with a case study as the research design. In collecting the data, the researchers utilized semi-structured interviews with two high-achieving and two low-achieving students in the 8th grade International Class Program at one of the private junior high schools in Malang, Indonesia. After gaining the data, the researchers analyzed it through three phases: familiarizing and organizing, coding and reducing, and interpreting and representing. The results showed that students respond positively to Baamboozle for vocabulary learning. Their perceptions are then categorized into seven points: 1. Using Bamboozle is an effective way to learn vocabulary; 2. The use of technology in the learning process is important; 3. Learning vocabulary using Baamboozle is more enjoyable; 4. The use of Baamboozle can increase vocabulary; 5. Favorite features of Baamboozle; 6. Students’ difficulties in using Baamboozle; 7. Baamboozle motivates students to learn vocabulary. Thus, utilizing technology-based gamification using Baamboozle is recommended in learning English vocabulary.